Geography of inbound tourism and transboundary tourism-and-recreation region-building in Sweden - Andrei G. Manakov; Irina N. Krasilnikova; Ivan A. Ivanov (Baltic Region, 2021)
Sweden’s tourism industry stands out for its large contribution to the development of the national economy. The vast size of the country makes it possible to trace differences in incoming tourist flows from neighbouring countries. This circumstance accounts for the novelty of this study, which lies in viewing national tourism geography from the perspective of the theory of transboundary tourism-and-recreation region building. Interregional differences in the structure of incoming tourist flows help identify the country’s cross-border tourism-and-recreation regions and delineate their borders. This research employs statistical and cartographic methods. The incoming tourist flow to Sweden grew steadily until 2020. However, the Covid-19 crisis has led to a drastic reduction in the number of incoming tourists. Based on the 2019 statistics, the findings confirm the existence of a developed transboundary tourism-and-recreation mesoregion that brings together Germany, Denmark, and Sweden. The formation boasts strong tourist links. There are another five cross-border tourism-and-recreation mesoregions: Sweden-Norway-Denmark, Middle Sweden-Norway, Sweden-Norway-Finland, Middle Sweden-Finland, and South Sweden-Finland. The number of tourists visiting cross-border mesoregions indicates the degree of development of the latter.